1999
DOI: 10.1080/016502599383900
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Family Resources and Satisfaction with Division of Labour on Coping and Worries after the Birth of the First Child

Abstract: Data on spouse support, family environment (cohesion and conflict), worries and depressed mood, parental coping, ”nancial resources, and employment status were recorded longitudinally by means of questionnaires among Swiss first-time parents. The first data collection was administered when the first-born child was aged between two and six months, the second one year later. Both mothers ( n = 164) and fathers ( n = 164) completed separate questionnaires. Structural equation models suggested both cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Maternal reports of parenting stress, depression and worry are lower when couple relationship satisfaction is high and when women perceive their male partner as supportive (Feldman et al 1997;Florsheim et al 2003;Wicki 1999). If maternal depression does develop, recovery is predicted by a satisfying and supportive couple relationship (Pope et al 1998).…”
Section: Couple Relationships and Parenting Of Infantsmentioning
confidence: 95%
“…Maternal reports of parenting stress, depression and worry are lower when couple relationship satisfaction is high and when women perceive their male partner as supportive (Feldman et al 1997;Florsheim et al 2003;Wicki 1999). If maternal depression does develop, recovery is predicted by a satisfying and supportive couple relationship (Pope et al 1998).…”
Section: Couple Relationships and Parenting Of Infantsmentioning
confidence: 95%
“…Another reason is that parents with more disposable income are likely to buy services that help to reduce the amount of family work that has to be divided among the partners (Wicki 1999), so that high satisfaction with financial resources is related to less parenting strain. Wicki (1999) studied 164 couples in Switzerland on the impact of family resources and satisfaction with division of labour on coping and worries after the birth of the first child.…”
Section: Financial Worriesmentioning
confidence: 99%
“…Wicki (1999) studied 164 couples in Switzerland on the impact of family resources and satisfaction with division of labour on coping and worries after the birth of the first child. She found that the mothers' perception of family resources and their worries were both affected by the couples' satisfaction with the division of labour, which in turn was related to the perception of financial resources.…”
Section: Financial Worriesmentioning
confidence: 99%
“…This finding makes some sense, given that prior studies have established that in certain families, mothers respond negatively when fathers take on greater parenting involvement with young infants than mothers had envisioned (e.g., Goldberg & Perry-Jenkins, 2004;Hackel & Ruble, 1992). Hence, we saw the value in directly examining the relationship between the extent to which parents' prenatal wishes about childcare involvement were violated, and the nature and quality of observed coparenting dynamics that had begun to consolidate in their family.Although there have been some interesting perspectives on men's expectancies about and involvement in childcare labor, no consensus has emerged as to whether expectancy violations among men hold the same psychological salience as do expectancy violations for women (e.g., Blair & Hardesty, 1994;Cowan & Cowan, 1988;Croghan, 1991;Grote & Clark, 2001; HelmsErikson, 2001;Wicki, 1999). Perhaps this is because mothers are the ones who generally anticipate assuming less childcare-related work than they ultimately end up taking on while fathers generally end up doing less than they had predicted prenatally (e.g., Belsky, 1985;Ruble et al, 1988).…”
mentioning
confidence: 99%
“…Although there have been some interesting perspectives on men's expectancies about and involvement in childcare labor, no consensus has emerged as to whether expectancy violations among men hold the same psychological salience as do expectancy violations for women (e.g., Blair & Hardesty, 1994;Cowan & Cowan, 1988;Croghan, 1991;Grote & Clark, 2001;HelmsErikson, 2001;Wicki, 1999). Perhaps this is because mothers are the ones who generally anticipate assuming less childcare-related work than they ultimately end up taking on while fathers generally end up doing less than they had predicted prenatally (e.g., Belsky, 1985;Ruble et al, 1988).…”
mentioning
confidence: 99%